2014
DOI: 10.7554/elife.02812
|View full text |Cite
|
Sign up to set email alerts
|

Resting state functional connectivity in the human spinal cord

Abstract: Functional magnetic resonance imaging using blood oxygenation level dependent (BOLD) contrast is well established as one of the most powerful methods for mapping human brain function. Numerous studies have measured how low-frequency BOLD signal fluctuations from the brain are correlated between voxels in a resting state, and have exploited these signals to infer functional connectivity within specific neural circuits. However, to date there have been no previous substantiated reports of resting state correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

31
166
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(203 citation statements)
references
References 57 publications
31
166
6
Order By: Relevance
“…Spinal gray matter horns are highly functionally connected at rest, to a much greater degree than has been previously recognized. Strong dorsal horn-to-horn connectivity was found in our study in anesthetized monkeys as well as in the two very recent studies in awake humans using different analytic methods (6,7). However, the specific horn-to-horn functional connectivity patterns within and across segments varied from the current study.…”
Section: Discussion Widespread Fmri Responses To Noxious Stimuli Withsupporting
confidence: 47%
See 2 more Smart Citations
“…Spinal gray matter horns are highly functionally connected at rest, to a much greater degree than has been previously recognized. Strong dorsal horn-to-horn connectivity was found in our study in anesthetized monkeys as well as in the two very recent studies in awake humans using different analytic methods (6,7). However, the specific horn-to-horn functional connectivity patterns within and across segments varied from the current study.…”
Section: Discussion Widespread Fmri Responses To Noxious Stimuli Withsupporting
confidence: 47%
“…The current study extends these ideas from the brain to the spinal cord. Our findings indicate that baseline functional connectivity is a common organizational feature within the central nervous system (6,7,30). Spinal gray matter horns are highly functionally connected at rest, to a much greater degree than has been previously recognized.…”
Section: Discussion Widespread Fmri Responses To Noxious Stimuli Withsupporting
confidence: 46%
See 1 more Smart Citation
“…This finding is interesting with regard to a seed-based resting-state study that observed stronger connectivity between ventral horns than dorsal horns (28) and two previous task-based spinal fMRI studies that showed a strong bilateral activation during motor tasks (43), but a clearly lateralized activation during painful sensory stimulation (37). Although such correspondence between task-related and resting-state spinal fMRI signals might be incidental, there is also evidence for a close correspondence of task-related and resting-state networks in the brain (10).…”
Section: Discussionmentioning
confidence: 81%
“…Performing it before temporal filtering is acceptable, but performing it after temporal filtering will lead to reintroduction of noise into the timeseries and inflated correlations; if it is necessary for nuisance regression to be performed after temporal filtering, then one should apply the same filter to the nuisance regressors themselves. It is reassuring to see that previous spinal cord resting-state studies did not fall prey to this mistake when using nuisance regression (Barry et al, 2016(Barry et al, , 2014Kong et al, 2014). Second, the use of low-pass or bandpass filtering is questionable, as several recent brain imaging studies have shown that frequencies above the common cut-off of 0.1Hz do contain meaningful signal (e.g.…”
Section: Discussionmentioning
confidence: 99%